Efeitos da higienização brônquica nas variáveis cardiorrespiratórias de pacientes em ventilação mecânica - Ambrozin, Alexandre Ricardo Pepe [UNESP] (2013)
INTRODUCTION: During mechanical ventilation (MV), the airways may accumulate secretions. Patients are submitted to Respiratory Therapy (RT) and tracheal aspiration when in MV, alone or associated, to eliminate these secretions. OBJECTIVE: The objective was to compare the effects of different protocols of bronchial hygiene in blood pressure, heart rate, oxygen saturation and respiratory rate of patients undergoing MV. MATERIALS AND METHODS: We conducted a prospective, randomized, controlled crossover, with intentional non-probabilistic sample in the Medical School Hospital of Marília. We included patients in invasive MV who were submitted to three different bronchial hygiene protocols: PP - physiotherapy protocol (manual chest compression and manual hyperinflation); AP - aspiration protocol; and PP + AP. Respiratory rate, systolic blood pressure (SBP), diastolic blood pressure (DBP), oxygen saturation and heart rate were evaluated in three moments: before (M1), immediately after (M2) and 30 minutes after (M3) for each protocol. The differences among protocols and times were assessed using ANOVA and post hoc Student Newman-Keus (p < 0.05). RESULTS: We studied eighteen 71.2 ± 13.9 year-old patients with 15.1 ± 17.7 days of MV. There were no differences among protocols. There was a significant decreasing in SBP (p = 0.0261) and DBP (p = 0.0119) from M2 to M3 in the aspiration protocol. CONCLUSION: There was a decrease of blood pressure on MV patients after 30 minutes of aspiration and no change in the other variables, and there was no difference among protocols.